Modern Internal Auditing–The New Profession. - Sawyer, Lawrence B. (The Accounting Review, 1975)
Abstract Features the accounting profession, Modern Internal Auditing. Signs which herald the advent of the profession; Analysis of the fields covered by Modern Internal Auditing; Career opportunities for Business Administration graduates; Pressures for formal education in Modern Internal Auditing.